2023
DOI: 10.1039/d3ta00097d
|View full text |Cite
|
Sign up to set email alerts
|

On the direct correlation between the copper current collector surface area and ‘dead Li’ formation in zero-excess Li metal batteries

Abstract: The direct correlation between the surface area of the current collector (CC) and the ‘dead Li’ is evaluated in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Through an insightful analysis of the correlation between surface area of 3D Cu current collectors and dead lithium, Adhitama et al elucidated the relationship between surface area and charge flux concentration, underlining the potential of larger surface areas to alleviate inhomogeneous lithium plating. 88 They compared three types of Cu current collectors (Fig. 12a) and found that the modified 3D Cu CC with a high-depth microstructure or large surface area can induce better electrochemical properties, displayed in Fig.…”
Section: Development Of Current Collectors Towards Homogeneity Of Lit...mentioning
confidence: 99%
“…Through an insightful analysis of the correlation between surface area of 3D Cu current collectors and dead lithium, Adhitama et al elucidated the relationship between surface area and charge flux concentration, underlining the potential of larger surface areas to alleviate inhomogeneous lithium plating. 88 They compared three types of Cu current collectors (Fig. 12a) and found that the modified 3D Cu CC with a high-depth microstructure or large surface area can induce better electrochemical properties, displayed in Fig.…”
Section: Development Of Current Collectors Towards Homogeneity Of Lit...mentioning
confidence: 99%